Cucurbit[8]uril facilitated Michael addition for regioselective cysteine modification. Issue 49 (26th May 2021) - Li, Gao; Hu, Jun; Chen, Huai; Chen, Yong-Xiang; Li, Yan-Mei
Abstract : Utilizing the interactions between tryptophan, methyl viologen and cucurbit[8]uril, distance between the targeted peptides/protein and the reactive peptide could be shortened, facilitating the Michael addition reaction between cysteine and dehydroalanine. Abstract : Utilizing the interactions between tryptophan, methyl viologen and cucurbit[8]uril, we found that the distance between the targeted peptides/protein and the reactive peptide was shortened, which facilitated the Michael addition reaction between cysteine and dehydroalanine. The highest acceleration was observed on cysteines with suitable p K a and spatial location to tryptophan, suggesting that our system can be used for regioselective cysteine modification.